Teaching Second National Language in Sri Lanka: Policy and Practice - Sabaratnam Athirathan; Markandu Karunanithy (University of Jaffna, 2014)
Sri Lanka is a multi-ethnic and multi-cultural country which had faced ethnic conflict in the past three decades without mutual understanding and communication between the two major Language speaking communities. Government of Sri Lanka has introduced teaching of Second National Language (2NL) (Sinhala/Tamil) as a compulsory subject in secondary school curriculum since 1998. Being a multi-ethnic, multi-religious and a pluralistic society, it is incumbent upon every Sri Lankan to learn a National Language other than his or her own. The two languages are to be taught to all children in all government schools as part of the curriculum. However, the implementation of this policy has been difficult because of the inability of teachers to teach 2NL (World Bank, 2012). Objectives of the study are to (a) identify the existing policy for teaching 2NL in government schools (b) Identify the contemporary status regarding the practice of teaching and learning 2NL at secondary school level. This study was a descriptive survey based on Colombo and Piliyandala zones in Western Province. 100 students of Grades 6-9, 75 teachers and 16 principals were selected using stratified random sampling method. Data was collected using Questionnaire, FGD, observation and check list. Descriptive method was employed for data analysis. Findings of the study were no clear cut state policy regarding teaching 2NL, less qualified teachers, no special appointment for teaching 2NL; other subject teachers teach 2NL students’ spoken and listening skill development of students is very poor. Textbooks are not matching with the needs of students and classrooms are not equipped with modern teaching learning strategies and this situation is hindering effective learning – teaching practices of 2NL Tamil
Keywords: Policy; Second National Language; Teaching Learning practice